2001
DOI: 10.1002/1522-2683(200101)22:2<235::aid-elps235>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

New approaches for fabrication of microfluidic capillary electrophoresis devices with on-chip conductivity detection

Abstract: In practice, microfluidic systems are based on the principles of capillary electrophoresis (CE), for a large part due to the simplicity of electroosmotic pumping. In this contribution, a universal conductivity detector is presented that allows detection of charged species down to the microM level. Additionally, powderblasting is presented as a novel technique for direct etching of microfluidic networks. This method allows creation of features down to 50 microm with a total processing time (design to device) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
2

Year Published

2001
2001
2006
2006

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 21 publications
3
90
0
2
Order By: Relevance
“…Interestingly, however, the results presented in this study compare favorably with microchip cation separations under similar conditions reported by other researchers [27,41,49]. The plate numbers obtained by Pumera et al [41] for Na 1 are also on the order of 45 000-55 000 for applied field strengths of 100 to 1000 V/cm.…”
Section: Cation Separationmentioning
confidence: 99%
“…Interestingly, however, the results presented in this study compare favorably with microchip cation separations under similar conditions reported by other researchers [27,41,49]. The plate numbers obtained by Pumera et al [41] for Na 1 are also on the order of 45 000-55 000 for applied field strengths of 100 to 1000 V/cm.…”
Section: Cation Separationmentioning
confidence: 99%
“…Guijt et al [24] employed thin films and sacrificial etching to make silicon nitride/glass microchannels. Features etched into a silicon substrate had a thin film of silicon nitride deposited on top.…”
Section: Thin-film Sacrificial Layer Microfluidicsmentioning
confidence: 99%
“…Van den Berg and co-workers [85][86][87] have manufactured glass-chips for zone electrophoresis and demonstrated the detection or inorganic ions and peptides with embedded electrodes. Soper and co-workers [88] have designed a device in PMMA and shown the separation and sensitive detection of amino acids, proteins and DNA fragments with a built-in conventional contacting conductivity detector.…”
Section: Figure 5 Schematic Drawing Of a C 4 Dmentioning
confidence: 99%